1998
DOI: 10.1046/j.1365-2249.1998.00533.x
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous immunoglobulin-producing capacity of cultures from lupus patients and normal donors following depletion of cells expressing CD19 or CD38

Abstract: SUMMARYCells spontaneously secreting IgG or IgM (ISC) are present at a high level in the blood of patients with systemic lupus erythematosus (SLE). By use of magnetic-bead techniques, mononuclear cells from such patients and healthy donors were fractionated according to expression of CD19 or CD38 and the cell fractions were then cultured in the absence of added mitogen/antigen for 5/6 days. Supernatant IgG and IgM were determined and, in addition, in the CD38 experiments ISC were enumerated both before and aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…With regard to B lymphocytes, spontaneously activated B cells and polyclonal production of Ig including autoantibodies have been repeatedly demonstrated in the peripheral blood and in the bone marrow in SLE. [17][18][19][20][21] The identification of an expansion of peripheral plasma blasts is consistent with these previous findings.…”
Section: Discussionsupporting
confidence: 87%
“…With regard to B lymphocytes, spontaneously activated B cells and polyclonal production of Ig including autoantibodies have been repeatedly demonstrated in the peripheral blood and in the bone marrow in SLE. [17][18][19][20][21] The identification of an expansion of peripheral plasma blasts is consistent with these previous findings.…”
Section: Discussionsupporting
confidence: 87%
“…Previous studies have defined B cell subsets from inflamed secondary lymphoid tissue such as tonsil (5,(15)(16)(17)(18)(19) or the periphery of active-SLE patients (22)(23)(24)(25)(26) by expression of IgD and CD38. Of note, the current results confirm published studies that have demonstrated that B cells in the periphery of active-SLE patients express significantly higher levels of CD38 than B cells in the periphery of normal, non-autoimmune individuals (22,25,26).…”
Section: Discussionmentioning
confidence: 99%
“…Following activation in an antigen-and MHC-restricted manner, CD154-expressing T cells initiate the GC reaction by engaging CD40-expressing pre-switch IgD + or postswitch IgD -B cells, thereby inducing them to express early-activation markers (CD69 and CD154) and differentiation markers (CD38, CD5, and CD27) (5)(6)(7)(8)(9)(10) and to proliferate rapidly to form IgD + primary or IgDsecondary follicles, more commonly referred to as GCs (11). Previous studies have defined functional B cell subsets from inflamed secondary lymphoid tissue, such as tonsil (12)(13)(14)(15)(16)(17)(18)(19)(20)(21), or the periphery of active-SLE patients (22)(23)(24)(25)(26)(27)(28)(29) by expression of CD27 and CD5, as well as IgD and CD38. Specifically, B cells that are bright for CD38, CD27, or CD5 have been shown to be Ig-secreting plasma cells, and cells expressing a low level of CD38, CD27, or CD5 have been shown to be memory-cell intermediates in the differentiation pathway to Ig-secreting plasma cells.…”
Section: Introductionmentioning
confidence: 99%
“…The consequence of genetic dysregulation of B‐cell development might be the survival of aberrant B cells. In accordance, it was shown that peripheral B cells taken from SLE patients contain populations that spontaneously produce immunoglobulins and that they can mature into antibody‐secreting cells when cultured in vitro even in the absence of B‐cell differentiation activators 32 . We demonstrated here that the expanded mature B‐cell population in the BM of SLE‐afflicted mice is decreased following treatment with hCDR1, at least because of increased apoptosis of the cells, in which the expression of the death receptor, Fas, was up‐regulated, and the expression of the survival gene, Bcl‐xL, was down‐regulated (Fig.…”
Section: Discussionmentioning
confidence: 77%